Optimal infusion rate in antimicrobial therapy explosion of evidence in the last five years - Zhu, Ling-ling (Infect Drug Resist, 2018)
BACKGROUND: Sporadic studies in antimicrobial therapy have evaluated the effects of infusion rates on therapeutic and economic outcomes, and new findings may challenge the regular infusion regimen. METHODS: Focusing on studies comparing the outcomes of different infusion regimens, the relevant literature was identified by searching PubMed, Web of Science, and Scopus from January 1, 2013 to March 1, 2018. Papers were finally chosen using a PRISMA flowchart. RESULTS: Antimicrobials with the superiority of prolonged infusion to standard infusion in terms of efficacy and safety include meropenem, doripenem, imipenem, cefepime, ceftazidime, piperacillin/tazobactam, linezolid, and vancomycin. The strategy of concomitantly reducing total daily dose and prolonging infusion time may cause treatment failure (eg, imipenem). Extended infusion of piperacillin/tazobactam has pharmacoeconomic advantage over standard infusion. Prolonged infusion of voriconazole is inferior to standard infusion because of lower efficacy caused by pharmacokinetic changes. Comparable outcomes following standard infusion and continuous infusion were observed with norvancomycin and nafcillin. Factors determining whether prolonged infusion has a benefit over standard infusion include MIC of bacterial pathogens, bacterial density, diagnosis, disease severity, total daily dose, and renal function. CONCLUSION: To maximally preserve the effectiveness of current antimicrobials, effective interventions should be implemented to enhance the application of optimal infusion strategies. For reducing nephrotoxicity, prolonged infusion of meropenem is better than conventional infusion in neonates with Gram-negative late-onset sepsis, and continuous infusion of vancomycin is superior to intermittent infusion. For increasing efficacy, prolonged or continuous infusion of time-dependent antimicrobials (eg, meropenem, doripenem, imipenem, cefepime, ceftazidime, piperacillin/tazobactam, linezolid, and vancomycin) is an optimal choice. Nevertheless, such advantages may only be demonstrated in special clinical circumstances and special populations (eg, patients with a sequential organ failure assessment (SOFA) score≥9, respiratory tract infections, urinary or intra-abdominal infections, or infections caused by less susceptible pathogens would benefit from prolonged infusion of piperacillin/tazobactam).